FAKTOR PENYEBAB PERILAKU SODOMI PADA REMAJA (STUDI DI LEMBAGA PEMBINAAN KHUSUS ANAK PEKANBARU) - Ingrid Weddy Viva Febrya (SISI LAIN REALITA, 2020)
Deviant behavior of sodomy is not only did by man but also did by adolescents. Sodomies in young age would serving their punishment at the Children Correctional Institution (LPKA), which was previously called children correctional institution. This research was conducted to determine what factors are behind the sodomy behavior in adolescents. The research was conducted in January-March 2020, located in LPKA Pekanbaru, Penitentiary street No.04, Muara Fajar, Rumbai sub district, Pekanbaru City, Riau. This research used descriptive qualitative method. Data obtained qualitatively and will present in a descriptive way. The research subjects were two children assisted by inmates with sodomy cases. Subject characteristics consist of: 1) age about 15 years old, 2) last education on Primary School and 3) sodomy cases. Data collection were done by observation, in-depth interviews and documentation. Data analysis used triangulation, which analyzed the results of interviews between subjects, LPKA officers and the subject's family. The results of this research found that the factors causing adolescents to do sodomy are: 1. Lack of parental supervision, 2. Previous perpetrators were victims of sodomy committed by adults and felt vengeful so that they took it out on younger children, 3. Cause of porn videos of homo sexual that watched by the perpetrators.